Compositional and structural characteristics of pepsin-soluble type I collagen from the scales of red drum fish, Sciaenops ocellatus. (February 2022) - Chen, Sijin; Hong, Zhuang; Wen, Hongmei; Hong, Bihong; Lin, Rurong; Chen, Weizhu; Xie, Quanning; Le, Qingqing; Yi, Ruizao; Wu, Hao
Abstract: The type I pepsin-soluble collagen (type I PSC) from the red drum fish ( Sciaenops ocellatus ) scales was successfully purified by hydrophilic ultrafiltration (UF). The collagen purification process was appraised in depth and described in detail, respectively. Based on SDS-PAGE analysis, using proteomics analysis and Isoform-sequencing (Iso-Seq), it was confirmed to be the type I PSC, containing collagen α1 and α2 chains as the single components, with the absence of the non- collagenous proteins, non-type I collagens and potentially allergenic proteins. The type I PSC was verified to be non-denatured collagen monomers with integrated triple-helical structure using gel filtration chromatography (GFC), ion-exchange chromatography (IEC), reversed-phase HPLC (RP-HPLC), fourier transform infrared spectroscopy (FTIR), matrix-assisted laser desorption ionization-time of flight/mass spectrometry (MALDI-TOF/MS) and amino acid composition analysis. Thus, the accurate primary structures of the type I PSC with 100% matched peptide coverage were obtained for the first time. Additionally, our current study is the first to illustrate the protein component changes in collagen induced by hydrophilic UF and the primary structure changes in collagen molecules induced by pepsin solubilization. Graphical abstract: Image 1 Highlights: ● High electrophoretically pure collagen might contain other proteins in the α chains ● Hydrophilic UF could purify the type I PSC monomer with 100% matched peptide coverage ● Accurate primary structures of the type I PSC were obtained for the first time ● It is the first report about collagen primary structure changes induced by extraction ● Collagen compositional changes induced by purification were first illustrated